2004
DOI: 10.1111/j.1464-5491.2004.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, immunological and clinical characteristics in newly diagnosed Asian diabetes patients aged 12–40 years

Abstract: Young onset diabetes patients in Asia represent a heterogeneous group in terms of their clinical and biochemical characteristics and classical Type 1 diabetes is relatively uncommon. The 5-year follow up study will determine the progress of these patients and help to clarify the natural history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 34 publications
(43 reference statements)
6
24
2
1
Order By: Relevance
“…The evolving epidemic of obesity in youth as a result of global industrialization favoring energy conservation over energy expenditure is the main culprit for the increasingly younger age of diabetes development. Consistent with the role of insulin resistance in type 2 diabetes, development of cardiometabolic risk factors precedes the diagnosis of diabetes in a large proportion of patients (3,4).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The evolving epidemic of obesity in youth as a result of global industrialization favoring energy conservation over energy expenditure is the main culprit for the increasingly younger age of diabetes development. Consistent with the role of insulin resistance in type 2 diabetes, development of cardiometabolic risk factors precedes the diagnosis of diabetes in a large proportion of patients (3,4).…”
mentioning
confidence: 89%
“…In susceptible ethnic groups including Asians, type 2 diabetes has emerged as the predominant form of dysglycemia in childhood and adolescence (2)(3)(4)(5). The evolving epidemic of obesity in youth as a result of global industrialization favoring energy conservation over energy expenditure is the main culprit for the increasingly younger age of diabetes development.…”
mentioning
confidence: 99%
“…But in the case of females more Malays (35%) compared to Chinese (14%) and Indians (15%), had high WHR indicating central obesity. 13 Ramachandran et al showed in his studies that more upper body adiposity measured as waist hip ratio found in south Indian population to be a greater risk factor for type 2 diabetes than general obesity. Indians with low BMI have WHR comparable to the Mexican Americans who are obese.…”
Section: Discussionmentioning
confidence: 97%
“…In the study by C Y Pan et al, 47% patients were found to be overweight (using the European classification of BMI >25 kg/ m 2 as overweight) However, recent research has shown that obesityrelated illness such as hypertension, diabetes and cardiovascular diseases tend to occur at lower BMI values in Asians and this has led to the suggested BMI > 23 kg/m 2 as being overweight 13 . Accordingly, (67%) of patients in this study were found to be overweight and 47% patients obese.…”
Section: Discussionmentioning
confidence: 99%
“…Malays (including Filipinos) have a higher risk for developing pediatric T2DM than other Asian groups [52]. Hypertension is a prevalent comorbidity or complication among Malay children with T2DM for which prevalence is similar to that in developed countries [53].…”
Section: Hypertensionmentioning
confidence: 99%